Autonomia profissional de trabalhadores de saúde mental em centros de atenção psicossocial: sonhos, utopias e esperanças - Marinho, Lionara de Cássia Paim (2023)
The Psychosocial Care Centers (CAPs) are the main territorial devices in response to the dehumanizing practices meted out to people in psychological distress. They were instituted based on Ordinance GM/MS n.336/2002 and are now part of the Psychosocial Care Network as central devices in mental health care. The CAP mental health worker, while having among his attributions the promotion of user autonomy, is subject, as a public servant, to State regulations. Given this context, the general objective of this thesis is to understand how CAP mental health workers produce their professional autonomy. This is a participatory, exploratory research, with a qualitative approach, which was carried out with a team of nine mental health workers from a Psychosocial Care Center for Alcohol and Other Drugs, in a municipality in the interior of the state of Rio Grande do Sul, Brazil. The theoretical reference of this study was the thought of Paulo Freire. The data production was carried out through semi-structured interviews and Culture Circles. Nine interviews and seven Culture Circles were conducted between September 2021 and July 2022. The data were analyzed using the Culture Circle method itself. The research followed the ethical recommendations of Resolutions Nº 466/2012 and Nº 580/2018 and was submitted to the Ethics Committee for Research with Human Beings. It was possible to identify five major generative themes: Public service and its interfaces with bureaucracy, hierarchy, and management; Teamwork: team characteristics, team meetings, communication/dialogue, and resistance to change; Psychosocial care network and Mental Health Public Policy; Encounters potentially promoting autonomy and Freedom, knowledge, and Permanent Education. The results showed that despite the norms and laws present in the public service, the stability and regulations of this entity are important to support decisions and positions. Teamwork proved to be fundamental for managing the different situations and challenges that arise in routine services. There are many difficulties in the implementation of public mental health policy, however, there is a willingness of workers to face them when there is affinity with the area. Knowledge was pointed out as fundamental for the development of autonomy and permanent education as a valuable strategy for overcoming the challenges that arise. It is hoped that this study can contribute to strengthening the professional autonomy of CAPs workers, improving their practices in their daily work, as well as raising concerns/questions in the workers themselves regarding the topic addressed.